Desenvolvimento e caracterização nutricional de leite fermentado asinino - Cavalcanti, Natália Sufiatti de Holanda (2019)
Several researches focusing on donkey milk supplied have been carried out, since it has a similar composition to human milk and it is the best alternative as a substitute for breast milk, when compared to ruminant milk. Due to the high content of lactose, the donkey can be used in the manufacture of fermented milk, and the development of new technologies, with the use of donkey milk in the manufacture of products, an alternative of innovation in the market of dairy products, contributing to expand the consumption of donkey milk. Therefore, the present study aimed to develop a fermented milk from donkey milk, as well as to evaluate the nutritional value and physical and chemical characteristics of fresh donkey milk and fermented donkey milk. In addition, the impact of refrigerated storage (4 ° C, 21 days) on the characteristics of fermented milk was evaluated. This was elaborated through the addition of a thermophilic culture composed of Streptococcus salivarius subsp. thermophillus and Lactobacillus delbrueckii subsp. bulgaricus (0,4 g / L), stored under refrigeration (4 ± 1 ºC) and evaluated for 21 days for area characteristics, sugar profile, amino acids, fatty acids, minerals and viability of lactic acid bacteria. The fermented milk was more acid (lower pH values and higher titratable acidity) and presented lower lactose, mineral (calcium, phosphorous, magnesium, sodium, and zinc), and amino acid (mainly indispensable amino acids) contents than milk. Otherwise, it had a better fatty acid profile (lower saturated fatty acid content, and higher monounsaturated and polyunsaturated fatty acid contents). The fermented milk storage resulted in decreases in the lactose content, improvements in the amino acid profile, and maintenance of the mineral content. However, negative impacts were observed on the fatty acid profile. In conclusion, both fresh donkey milk and fermented donkey milk present important nutritional value, and the fermented milk could be refrigerated stored for 21 days.